(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The characteristics of the rare plant species, growing on the territory of the Kherson region (Ukraine) – 7 species of Algae, 10 species of Bryophyta, 1 species of Licopodiophyta, 4 species of Polypodiophyta, 1 species of Pinophyta and 107 species of Magnoliophyta is given in the article. It is pointed out in which nature preservation document each species is included.